Peer Judgement and Speaking Anxiety in English Oral Performance: A Micropolitical Perspective in the EFL Classroom - Diva Febiyanti; Sarlita D. Matra (FKIP, Universitas Palangka Raya, 2026)
One of the biggest issues that students in English as a Foreign Language (EFL) class still face is speaking anxiety, especially when it comes to oral performance exercises. The previous study has largely concentrated on internal psychological issues and has rarely investigated how students’ silence behavior during speaking activities is influenced by peer judgment and classroom micropolitics. Therefore, the purpose of this research was to find out how students’ fear oof making mistakes is influenced by peer judgement, whether micropolitical interactions influence students’ silence during oral performances and how the classroom environment influences students’ willingness to speak English. 26 eleventh-grade students from SMAN 1 Pekalongan participated in this study, which used a qualitative descriptive design. Thematic analysis was used to examine the data, which were gathered through open ended format questionnaire and classroom observation. The findings showed that students’ fear receiving a poor grade and speaking anxiety were elevated by peer judgement, which include laughing, whispering, gossiping and making fun of pronunciation errors. The findings also demonstrated how classroom micropolitics caused unequal participation patterns, with confident students taking the lead and less confident students choosing to keep quiet during oral performance. Also, the classroom environment had a significant impact on students’ desire to speak since students felt less confident while speaking in noisy and unsupportive settings. In general, peer interaction, the classroom environment and classroom micropolitical dynamics all contributed to the social construction of speaking anxiety.